2014
DOI: 10.1373/clinchem.2014.222331
|View full text |Cite
|
Sign up to set email alerts
|

Genomic High-Resolution Profiling of Single CKpos/CD45neg Flow-Sorting Purified Circulating Tumor Cells from Patients with Metastatic Breast Cancer

Abstract: BACKGROUND:Circulating tumor cells (CTCs) are promising surrogate markers for systemic disease, and their molecular characterization might be relevant to guide more individualized cancer therapies. To enable fast and efficient purification of individual CTCs, we developed a work flow from CellSearch TM cartridges enabling high-resolution genomic profiling on the singlecell level. METHODS:Single CTCs were sorted from 40 CellSearch samples from patients with metastatic breast cancer using a MoFlo XDP cell sorter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 27 publications
1
53
0
Order By: Relevance
“…Schneck and colleagues analyzed CTCs using the SNaPshot method and found PIK3CA mutations in enriched CTC pools of 15.9% of patients with metastatic breast cancer ( 80 ). Other authors isolated single CTCs and reported strong heterogeneity in the PIK3CA mutational status among CTCs from individual patients (81)(82)(83). These single CTC analyses resulted in higher detection rates of PIK3CA mutations; however, more information about the occurrence of these mutations in the context of therapeutic interventions is urgently needed.…”
Section: Dna Levelmentioning
confidence: 99%
“…Schneck and colleagues analyzed CTCs using the SNaPshot method and found PIK3CA mutations in enriched CTC pools of 15.9% of patients with metastatic breast cancer ( 80 ). Other authors isolated single CTCs and reported strong heterogeneity in the PIK3CA mutational status among CTCs from individual patients (81)(82)(83). These single CTC analyses resulted in higher detection rates of PIK3CA mutations; however, more information about the occurrence of these mutations in the context of therapeutic interventions is urgently needed.…”
Section: Dna Levelmentioning
confidence: 99%
“…An inevitable step therefore is to pick and isolate the single CTCs in individual tubes or as a pure CTC fraction for genomic analysis. Methods used to isolate single cell for individual analysis in combination with CellSearch-enriched CTCs: Micromanipulation [113], ALS Cellselector [114], the Silicon Biosystems DEPArray [115][116][117][118], FACS [28,119,120], and the Punch system using self-seeding Microwell Chips [121]. This step seems a minor intermediate part of the whole workflow but is crucial for the end result.…”
Section: Collection Of the Immunomagnetically Enriched And Fluorescenmentioning
confidence: 99%
“…This system is useful for bulk CTC enrichment but cannot be integrated directly with well plates for single cell molecular analysis. To overcome this, Neves et al 34 developed a protocol for CELLSEARCH® based CTC enrichment, FACS sorting and isolation into PCR tubes followed by single cell molecular analysis via qPCR. This study illustrated the combination of CELLSEARCH® and FACS for molecular analysis of single CTCs.…”
Section: Sample Preparationmentioning
confidence: 99%